IMPLEMENTATION OF REALISTIC MATHEMATICS EDUCATION BASED ON ADOBE FLASH PROFESSIONAL CS6 TO IMPROVE MATHEMATICAL LITERACY - Uba Umbara; Zuli Nuraeni (Jurnal Infinity, 2019)
Students' mathematical literacy abilities are important to master, especially to formulate mathematical concepts that can be used in everyday life. Mathematical literacy has become an important issue lately to be developed in the study of mathematics learning. However, mathematical literacy has not become the main goal in the implementation of the learning carried out. The purpose of this study was to examine the comparison of students 'mathematical literacy skills with Adobe Flash Professional CS6-based RME learning with conventional learning and to examine the comparison of improvement in students' mathematical literacy skills with Adobe Flash Professional CS6-based RME learning with conventional learning. The research method used in this study was quasi-experimental with the design of a non-equivalent control group design. The results of the two research hypotheses were accepted. It is possible that the increase in students' mathematical literacy skills is triggered by the Adobe Flash Professional CS6-based RME learning which in the implementation of learning always focuses on self regulated learning.